1839 Tex. Gen. Laws 214, An Act To Incorporate The City Of Austin, § 7 - (:unkn) unknown (My University, 1839)
That the Mayor and Counsel shall have full power and authority ... to prevent gunpowder being stored within the city and suburbs in such quantities as to endanger the public safety. . .
Keywords: GUNPOWDER - STORAGE